An introduction to the International Confederation of Sport and Exercise Science Practice and the need for global advocacy - Davison, K. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The International Confederation for Sport and Exercise Science Practice (ICSESP) was formed by the American College of Sports Medicine (ACSM), British Association of Sport and Exercise Sciences (BASES), Canadian Society for Exercise Physiology (CSEP), Exercise and Sports Science Australia (ESSA), and Sport and Exercise Science New Zealand (SESNZ) to promote and support the interests of Sport and Exercise Science (SES) practitioners across the world. To support this agenda, the ICSESP undertook a survey of practitioners worldwide to understand the context of their practice and the challenges and opportunities facing them in their roles locally and internationally. METHODS: The survey was developed by the representative directors of the five organisations who each have extensive national leadership in SES practice and links to international networks. The survey was promoted to practitioners through national organisation official media channels and via international member networks and social media (Twitter, Facebook), and was open for approximately 5 months from March to August of 2022. Context data were extracted and summarised descriptively and text responses about future opportunities and challenges were collated into common themes. RESULTS: A total of 750 people completed the survey, with 103 removed due to not having a tertiary degree background in SES, leaving 647 eligible responses. There were 37 discreet countries represented although the majority of responses (>90%) were from the ICSESP member countries of Australia, Canada, UK, USA and New Zealand. The predominant fields of practice were clinical exercise physiology (28%), exercise and sports science (25%), and Kinesiology (15%). The most common populations practitioners worked with were general healthy population (17%), musculoskeletal injury and disease (15%) cardiovascular disease (12%), sub-elite athletes (11%), metabolic disease (10%), and others including elite athletes, people with a disability, and people with a neurological disease, mental illness and cancers. The most pressing challenge identified was lack of recognition of the skills and qualification of SES practitioners, and the greatest opportunity was the increasing recognition of the role of exercise in improving and maintain health. CONCLUSION: There is evidence of degree qualified practitioners of SES in many parts of the world. Issues faced by practitioners are common across the world, which support the value of the ICSESP in advocating for these professionals globally. The international community of SES practitioners, educators and researchers can work together to lift the profile of this industry and reduce the global burden of non-communicable disease.